2017
DOI: 10.1038/s41598-017-15737-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of novel metabolites potentially involved in the pathogenesis of coronary heart disease using a UHPLC-QTOF/MS-based metabolomics approach

Abstract: Coronary heart disease (CHD) is associated with complex metabolic disorders, but its molecular aetiology remains unclear. Using a novel nontargeted metabolomics approach, we explored the global metabolic perturbation profile for CHD. Blood samples from 150 patients with severe obstructive CHD and 150 angiographically normal controls were collected. Metabolic fingerprinting was performed by ultra-high performance liquid chromatography coupled to quadruple time-of-flight mass spectrometry (UHPLC-QTOF/MS) techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 59 publications
(63 reference statements)
2
27
0
Order By: Relevance
“…For example, a recent development is the recognition of lipoprotein subclasses [ 50 , 51 , 52 ]. Related to this is the use of metabolomics for the identification of diverse substances associated with CHD [ 53 ]. This line of investigation may lead to the identification of new biomarkers that can serve as valuable tools in CHD research.…”
Section: Future Research Studiesmentioning
confidence: 99%
“…For example, a recent development is the recognition of lipoprotein subclasses [ 50 , 51 , 52 ]. Related to this is the use of metabolomics for the identification of diverse substances associated with CHD [ 53 ]. This line of investigation may lead to the identification of new biomarkers that can serve as valuable tools in CHD research.…”
Section: Future Research Studiesmentioning
confidence: 99%
“…In our result, PG (16:1/16:1) and PG (18:3/20:4) are DNB molecule candidates in 14 samples of the Stage A group (15 samples in total), which reveals the importance of PGs in the progression of coronary atherosclerosis, and their specific molecular mechanisms need to be further studied. Palmitic acid, a molecule involved in fatty acid metabolism, has been reported to be intimately related to cardiovascular disease [ 29 , 33 , 34 ]. The metabolic dynamic changes caused by palmitic acid intake can influence the levels of total cholesterol and low-density lipoprotein (LDL) cholesterol, which show a strong positive correlation with the development of coronary heart disease [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies [6,[28][29][30] have shown that ALSSs therapy can remove harmful substances from the body, maintain homeostasis, temporarily assist or replace liver function, facilitate hepatocyte regeneration and recovery of liver function, and improve the survival rate of patients with liver failure. Hu P. [11] found that levels of ALB, creatinine, TBIL, INR, PTA, and ALT in serum changed signi cantly before and after ALSSs treatment. Hu S. et al [13] explored the curative effect of hybrid-bioarti cial liver on patients with liver failure related to infection by hepatitis B virus, and found that ALT, ALB, and TBIL were signi cantly altered after ALSSs treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Metabonomics has developed rapidly over more than a decade, achieving great results in disease diagnosis, drug research and development, and other elds of human health care [10][11][12][13][14]. Yang L. et al adopted for metabolomics analysis a rat model in which liver failure was induced by application of tetrachloromethane and alpha-naphthylisothiocyanate.…”
Section: Introductionmentioning
confidence: 99%